2019
DOI: 10.1021/acs.iecr.9b05520
|View full text |Cite
|
Sign up to set email alerts
|

PC-SAFT Parameter Correlations from Simple Measurements at Ambient Conditions for Predictive Modeling of Nonpolar Hydrocarbons

Abstract: New correlations for calculating the simulation parameters of the perturbed-chain version of the statistical associating fluid theory (PC-SAFT) equation of state for nonpolar hydrocarbons are presented in this work. The three PC-SAFT simulation parameterssegment number (m), segment diameter (σ), and segment–segment interaction energy (ε/k)are correlated to molecular weight and density at 20 °C for a database of 46 components containing n-alkanes, benzene derivatives, and naphthalene derivatives. The accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Comparison of Cases I–III model predictions of saturated liquid density to DIPPR correlations. Green dashed‐dotted curve gives model predictions using PC‐SAFT petroleum fraction parameters obtained through the method of Abutaqiya et al 21 [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Extension Of Tapps To Vacuum Residuum Range Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of Cases I–III model predictions of saturated liquid density to DIPPR correlations. Green dashed‐dotted curve gives model predictions using PC‐SAFT petroleum fraction parameters obtained through the method of Abutaqiya et al 21 [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Extension Of Tapps To Vacuum Residuum Range Moleculesmentioning
confidence: 99%
“…In general, Case I will give much more accurate vapor pressures than Case III; however, density predictions are similar between the two approaches. For comparison, model predictions using the recent PC‐SAFT petroleum fraction parameter estimation methodology of Abutaqiya et al 21 were included. As can be seen, this methodology gives reasonable predictions for the density of hexylbenzene, but substantially underpredicts the density of pyrene.…”
Section: Extension Of Tapps To Vacuum Residuum Range Moleculesmentioning
confidence: 99%
“…Comparison of PC-SAFT predictions of binary VLE using only petroleum variables T b , SG, and MW to describe the hydrocarbons. The solid lines are predictions from TAPPS, the dotted lines are predictions using the method of Yan et al, 54 and the dashed lines are predictions using the method of Abutaqiya et al 55 Experimental data are shown as circles: naphthalene/n-dodecane, 50 phenanthrene/n-hexadecane, 51 3methylpentane/methylcyclohexane, 52 and propylbenzene/n-nonane. This general approach to petroleum pseudocomponent parametrization (previously called EMPETRO) will now be referred to as The Advanced Petroleum Parameterization Scheme (TAPPS).…”
Section: Pc-saftmentioning
confidence: 99%
“…These predictions are compared to experimental data for several binary mixtures in Figure . For comparison, we have also included predictions using the parametrization methodologies of Yan et al and Abutaqiya et al There have been several other attempts to develop PC-SAFT parameters for ill-defined mixtures, but these other approaches lack sufficient accuracy to even be comparable on the scales of Figure . This figure shows that although the approaches of Yan et.…”
Section: Modelsmentioning
confidence: 99%
“…Additionally, several authors have reported that F RI,20 and ρ 20 are actually related for petroleum fractions. , This implies that the ratio F RI,20 /ρ 20 can be written in terms of only one of the variables ( F RI,20 or ρ 20 ), whereas at least two independent bulk properties are required to describe the molecular size and molecular interactions for each component to be able to distinguish between different hydrocarbon families. Our application of the Modarress and Vakili-Nezhaad characterization factor for the hydrocarbon database used in this investigation , yields ranges of 0.334–0.350 for n -alkanes, 0.329–331 for naphthenes, and 0.333–0.345 for aromatics, which shows overlap between n -alkanes and aromatics.…”
Section: Introductionmentioning
confidence: 99%